1955
DOI: 10.1017/s0021859600039952
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic irregularities in hexaploid oats IV. Hybrids between Avena sativa (spring and winter varieties) A. fatua, A. sterilis, A. byzantina and A. nuda

Abstract: 1. Pollen mother cells with irregularities of meiosis were rare in the parent species and varieties, being usually less than 0·5% and the highest found being only 1·57% in the variety Grey Winter.2. F1A. fatua C.S. 473 (from Afghanistan) × Grey Winter had 33·5% of pollen mother cells with irregularities. On the other hand, the F1 hybrids of A. fatua (C.S. 46 (from Asia Minor) × both spring and winter varieties of A. sativa showed between 2·45 and 12·81% of irregular cells and were thus more regular than F1 spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1956
1956
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In another study, Joshi et al also reported the detection of an olive oil mixture in argan oil by using portable Raman spectroscopy. 80 The analysis of EVOO combined with grapeseed and canola oils at 0–100% was performed using a short distance standoff Raman detection instrument attached to a 785 nm laser source. 81 Further, Raman spectroscopy with exponential equations has been used to predict the adulteration in olive oil.…”
Section: Detection Of Food Adulterantsmentioning
confidence: 99%
“…In another study, Joshi et al also reported the detection of an olive oil mixture in argan oil by using portable Raman spectroscopy. 80 The analysis of EVOO combined with grapeseed and canola oils at 0–100% was performed using a short distance standoff Raman detection instrument attached to a 785 nm laser source. 81 Further, Raman spectroscopy with exponential equations has been used to predict the adulteration in olive oil.…”
Section: Detection Of Food Adulterantsmentioning
confidence: 99%